A novel energy-efficient machine to compress inorganic residues in eco-bricks as a sustainable construction strategy for low-cost housing (2019)
UNESCO has set the Sustainable Developing Goals (SDG) to promote good practices in different areas. The construction industry has evolving to the use of alternative and eco-friendly materials, enhancing the sustainable growth of the cities. One of the main social problems in developing countries arises on the lack of housing at affordable prices, this is reflected as a result of a situation of poverty and exclusion of low-income communities. The present work describes the development of a novel device for the compression of plastic waste in PET bottles, also denominated eco-bricks. The device allows the compaction of plastic laminates and sachets inside bottles of different sizes. Based on a social context, the compactor device was designed for manual operation without the use of electric power, portability, ease of usage and safe operation. Another outcome of this technology is the educational strategy based on the manufacturing of eco-bricks that promotes environmental responsibility that aims at reducing pollution and the indiscriminate and non-responsible use of non-renewable resources in urban and rural environments. The device was submitted for its consideration as an invention patent and therefore granted. © 2019 AISTI.